Material discard reasons: Categorising and characterising industrial waste materials - Sander, Nikoline; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper investigates industrial waste and its characteristics from a design perspective with the objective of assessing why so many materials are discarded. Industrial waste emerges pre-consumer and poses potential as material resources for new product designs on an industrial scale. Most research assesses post-consumer waste, but more than 230 million tons of waste emerge from manufacturing, hence pre-consumer. Current research on industrial waste divides it into scraps and rejects with varying characteristics of predictability and seriality. We add to the research through a two-year research project on designing with industrial waste from Danish manufacturing companies. Through observations, registrations, and semi-structured interviews, we study 24 discarded material cases and assess the challenges for industrial design. From a designer’s perspective, we investigate where and why materials are discarded, the categories, and how they can be further characterised. The result is a division of industrial waste into five types: 1) offcuts, 2) rejected materials, 3) rejected objects, 4) process waste, and 5) excess material. They vary in predictability, uniformity, presence of flaws, and data availability. These are characteristics that designers must consider when extending the material lifetime and keeping the material at its integrity level in new product designs.